Pengaruh Strategi Predict Observe Explain (POE) Terhadap Kemampuan Berpikir Kritis Siswa: The Impact of Predict Observe Explain (POE) strategy against student's critical thinking ability - Gufron Amirullah; Rizkia Suciati; Susilo Susilo; Dewi Handayani (BIODIK, 2019)
Learning strategy is a very decisive factor in student learning outcomes. This study wanted to know the influence of Predict Observe Explain (POE) strategy to the critical thinking ability of grade X students in environmental pollution material at SMA Negeri 3 Bekasi. The study used Pretest-Posttest Control Group Design with a sampling technique of Cluster Random Sampling (N: 90). Research instruments in the form of 10 test descriptions that have been integrated with the ability of critical thinking are used for data collection. The research Data is analyzed using the normality test, homogeneity test, and T test. Our research results show the average value of the experiment class (x = 75.03) greater than the control class (x = 65.57). The hypothesis Test (T-Test) with a signification level of 1% obtained a Thit value of 5.25 & this 2.39. Our research suggests that POE learning strategies can affect students ' critical thinking skills. This POE strategy can be used as a referral for biological teachers to improve the students ' critical thinking skills. Keywords: POE strategy, essential thinking ability, environmental pollution. Abstrak. Strategi pembelajaran merupakan faktor yang sangat menentukan hasil belajar siswa. Studi ini ingin mengetahui pengaruh strategi Predict Observe Explain (POE) terhadap kemampuan berpikir kritis siswa kelas X pada materi pencemaran lingkungan di SMA Negeri 3 Bekasi. Penelitian ini menggunakan Pretest-Posttest Control Group Design dengan teknik sampling Cluster Random Sampling (n: 90). Instrumen penelitian berupa 10 soal tes uraian yang telah terintegrasi dengan kemampuan berpikir kritis digunakan untuk pengumpulan data. Data penelitian dianalisis dengan menggunakan uji normalitas, uji homogenitas, dan uji t. Hasil penelitian kami menunjukkan nilai rata-rata kelas eksperimen (x = 75,03) lebih besar dari kelas kontrol (x = 65,57). Uji hipotesis (uji t) dengan taraf signifikasi 1 % diperoleh nilai thit sebesar 5,25 & ttabel 2,39. Penelitian kami menunjukkan bahwa strategi pembelajaran POE dapat mempengaruhi kemampuan berpikir kritis siswa. Strategi POE ini dapat dijadikan rujukan guru biologi untuk meningkatkan kemampuan berpikir kritia pada siswa. Kata Kunci : Strategi POE, Pencemaran Lingkungan, Kemampuan Berpikir Kritis.